Catalytic oxidation of dopamine: mushroom tyrosinase vs. dinuclear copper(II) complex - Sýs, Milan; Mikysek, Tomáš; Novák, Miroslav (BEST Servis, 2021)
The aim of this scientific study was to compare catecholase activity (representing the ability to oxidize ortho-diphenols) of tyrosinase enzyme (isolated from the common mushroom Agaricus bisporus) with a completely synthetic dinuclear copper complex toward the neurotransmitter dopamine using standard Michaelis-Menten kinetics model. Both, standard UV–Vis spectrophotometry and amperometry in a batch configuration were presented as complementary methods to study the catecholase activity. Despite the finding of comparable catalytic activity (similar Michaelis–Menten constants), it is necessary to mention that tyrosinase enzyme is not active in methanol solution like investigated dinuclear copper(II) complex.
Katalytická oxidace dopaminu: houbová tyrosináza vs. dvojjaderný komplex mědi (II)
Keywords: catecholase activity; dopamine; tyrosinase; amperometric detection; katecholázová aktivita; dopamin; tyrozináza; amperometrická detekce